Die Maleierkamp van Kimberley 1882 - 1957 - Africa, Edward John (University of the Free State, 1992)
Shortly after the discovery of the dry diggings, the London and South African Exploration Company was registered in order to acquire lands in South Africa for mining and exploring In March 1871, the London and South African Exploration Company and the Hopetown Diamond Company merged into a limited liability company under the former title. Their head office was in London, with a local office in, Kimberley. J.B. Currey, the local manager, was responsible for reporting to the London Board of Directors, which formulated the company's policy. The property comprised the farms Bultfentel n, Dorstfontein and Alexanderfontei n. The townships of Beaconsfield and Newton formed part of the estate. By the issue of proclamation no. 71 of 1871, portions of the farms Vooruitzight, Bultfontein and Dorstfontein were declared public diggings in October 1871. The influx of fortune-seekers and unskilled Iabourers resulted in a large cosmopolitan population arising on the diggings. The huge demand for labour, and the comparatively high wages attracted thousands of migrant Natives. The accumulation of a large heterogeneous population led to the emergence of a permanent proletariat. There was a marked increase in crime, and the maintenance of law and order placed high demands on the limited police force. A band of exceptionally dedicated clergymen from various denominations grasped the opportunity to spread the Gospel amongst the diversified population. Since the inception of the diamond fields, the inhabitants occupied stands, erven and holdings at Bultfontein, Dorstfontein and Newton under leasehold, tenure or licences. Under this form of licence, the tenant had no proprietary right. The Malay Camp was entirely leasehold property. It was situated in the Newton township in the middle of the estate. The camp was started by Malay transport drivers who flocked to the diggings in search of work or in the hope of wealth. Originally the Malay Camp was more or less an exclusive Muslim residential area. This was the best residential portion of Kimberley. Gradually Newton became occupied principally by coloured people and Mohammedans, both of Indian and Cape extraction. After 1880 the Malay Camp developed into a densely populated racially mixed residential area. Even in the best of times, the Malay Camp was justly considered one of the worst slums in South Africa. The unfortunate poverty-stricken inhabitants were forced to live in run-down hovels unfit for human habitation. The overcrowded, squalid neighbourhood was the most vulnerable in times of epidemics. Gradually a growing consensus took root among whites regarding the removal of non-whites from the Malay Camp to municipal native locations and segregated residential areas on the outskirts of Kimberley. The petitioners lodged complaints with the authorities about the lack of sanitary facilities, the appalling housing conditions and the fear for the outbreak and spreading of infectious diseases. Councillors and health officers were resolute as to the removal and demolition of the dilapidated Malay Camp. On 22 September 1899, the De Beers Consolidated Mines, Ltd. purchased the properties of their former landlords, the London and South African Exploration Company. By virtue of the Deed of Donation, the City council became the rightful owner of the De Beers Estate. In terms of clauses 10 and 11 of the Deed of Donation the municipality undertook - and bound itself - to terminate and cancel all stand licences held by non-Europeans by 31 December 1953, without prior consultation or negotiations with the Malay Camp residents, and to demolish the area not later than 31 December 1959. The official notice to quit was strongly condemned by the standholders. The said racial discriminatory clauses of the agreement were criticized by the perturbed community. The implementation of the Slum Act and the Group Areas Act precipitated the clearance and demolition of the Malay Camp. The slum clearance which was started in the 1940's, made way for the development of the new Cïvic Centre. The centre was to provide a complex for Kimberley's social, cultural and administrative activities. It arose from the rubble where some five hundred decaying houses were occupied by the poorer non-European groups for some eighty years, prior to the forced removal and disintegration of a cosmopolitan society and the establishment of a municipal administrative conglomerate.

Kort ná die ontstaan van die droëdelwerye in Griekwaland-Wes is die London and South African Exploration Company op 21 November 1870 in Londen gestig. In Maart 1871 het die Hopetown Diamond Company en die London and South African Exploration Company geamalgemeer in 'n publieke maatskappy met beperkte aanspreeklikheid onder laasgenoemde titel. Die beheer van die maatskappy is behartig deur 'n direksie vanuit sy geregistreerde hoofkantoor in Londen. Die bestuurder in Kimberley, J.B. Currey, was direk verantwoordelik aan sy Londense direkteure. Die maatskappy se eiendomme het bestaan uit die' plase Bultfontein, Dorstfontein en Alexanderfontein. Die dorpsgebiede Beaconsfield en Newton het deel uitgemaak van die landgoed. Die plase Vooruitzigt, Dorstfontein en Bultfontein is in Oktober 1871 tot openbare del werye verklaar. Duisende fortuinsoekers en arbeiders het na die diamantvelde gestroom wat gelei het tot die totstandkoming van 'n groot kosmopolitiese bevolking met die bygevolge politieke en sosio-ekonomiese vraagstukke. Die vraag na ongeskoolde arbeiders en die betreklike hoë loongeld was die aanleidende oorsake vir die skepping van 'n permanente nie-blanke proletariaat. Die konsentrasie van 'n horde nasionaliteite, saamgestel uit verskeie etniese groepe, het 'n gees van onrus laat posvat en voorheen onbekende misdade het hul verskyning gemaak. Die handhawing van wet en orde op die diamantvelde het hoë eise aan die staat gestel. Skerpsinnige predikante en kerkgenootskappe het die geleentheid aangegryp om die evangelie aan die heterogene massas te verkondig. Terwyl Du Toitspan en Bultfontein in privaatbesit was, is standplaaslisensies op bepaalde voorwaardes aan die inwoners verhuur. Die lisensiesteisel van grondbesit het geen sekuriteit van eiendomsbesit gewaarborg nie. Die Maleierkamp geleë op die De Beers-landgoed, was geheel en al verpagte eiendom. Die Maleierkamp was geleë in Newton. Die Maleierkamp was die mees sentraal- geleë en waardevolste residensiële woongebied in Kimberley. Vóór 1880 was dit oorwegend 'n eksklusiewe Moslem-woongebied. Die Maleiers het 'n eiesoortige leefwyse gehandhaaf gebaseer op hul godsdienstige oortuigings. In die Maleierkamp was daar moskeë waar die Mohammedane hul geloof met stiptelikheid beoefen het. Mettertyd het die Maleierkamp ontwikkel tot 'n digbevolkte, veelrassige woongebied waar blankes, swartes, Asiërs en Kleurlinge hul permanent gevestig het. Die Maleierkamp is tereg bestempel as van die ergste agterbuurtes in Suid-Afrika. In dié oorbevolkte woongebied het mense in haglike lewensomstandighede 'n sukkeIbestaan gevoer. Gaandeweg het 'n ontluikende konsensus in blanke geledere oor die verwydering van nie-blankes uit die Maleierkamp na swartlokasies óf apartheidswoongebiede, posgevat. Klagtes oor die krotwoonbuurttoestande, gebrekkige sanitasie, die gevaar van siekte epidemies 'het toegeneem en is ondersteun deur die georganiseerde optredes van munisipale gesondheidsbeamptes. Op 22 September 1899 het die De Beers Consolidated Mines, Ltd. die eiendomme van die London and South African Exploration Company aangekoop. Kragtens die Deed of Donation van 1939 het die Kimberleyse stadsraad, as regopvolgers van die De Beersmaatskappy, volle eiendomsreg van die De Beerslandgoed verkry. Behoudens die bepalinge van klousules 10 en 11 van die De Beerslandgoed-ooreenkoms het die stadsraad, sonder vooraf beraadslaging met die Maleierkamp-bewoners, hom onherroeplik en onvoorwaardelik daartoe verbind om alle huurkontrakte van nie-blankes woonagtig in die Maleierkamp teen 31 Desember 1953 te beëindig, asook om die gebied teen 31 Desember 1959 te sloop. Die kennis van huuropsegging het hewige teenkantig van die Maleierkamp-bewoners ontlok. Die aanvaarding van die rasse-diskriminerende bepalings van die skenkingsakte is skerp veroordeel. Die toepassing van die Slumswette en die Groepsgebiedewet het die sloping van die Maleierkamp verhaas. Die agterbuurtopruiming is in die veertigerjare van stapel gestuur. Die ontwikkeling van die nuwe burgersent'rum het vroeg in die vyftigerjare begin. Die burgersentrum, wat verrys het op die terrein van die gewese Maleierkamp, was bestem om die tuiste te word van Kimberley se belangrikste sosiale, kulturele en administratiewe aktiwiteite.
Dissertation (M.A. (History))--University of the Free State, 1992
Keywords: Malay Camp -- South Africa -- Kimberley; Missions -- South Africa -- Kimberley, 1882-1957; Malays (Asian people) -- South Africa -- Kimberley, 1882-1957; Muslims -- South Africa -- Kimberley, 1882-1957